(untitled) (ESMAT Magazine, 2024)
The objective of this work is to explore the evolution of artificial intelligence, its use in different countries and its risks and benefits, with the research focusing on studying the application of artificial intelligence within the Judiciary. Thus, the problem arises: can automated decisions made by artificial intelligence be considered reliable and neutral? Understanding the consequences of using automated decisions in the judicial system, how it is being implemented in the most varied social sectors, and how this developing technology should be used are factors discussed within this work. Using the inductive method, the research addresses the concept of artificial intelligence, its origin and history to the present day, its functioning, its national and international applications, focusing on Superior and Federal Courts, and examines the benefits and risks of the technology, including “algorithmic morality”. To achieve this, the work will make use of doctrines, scientific works and legislative matters, also elucidating and reflecting the topic based on concrete cases, in order to reach conclusions on the topics raised.